First reported case of Human Parechovirus encephalitis in an adult patient complicated by Refractory Status Epilepticus. (2019) - Chimunda, Timothy; Subramanian, Rakhee; Smith, Julie; Mahony, Andrew
Highlights: Human Parechovirus (HPeV) infections are common amongst young children. However, data in adult cases are lacking. We report a unique case of HPeV meningoencephalitis in an adult complicated by Refractory Status Epilepticus (RSE). This case expands the epidemiological knowledge of HPeV and when to test for it in adults. Abstract: Human Parechovirus (HPeV) infections are common amongst children, particularly neonates. However, data in adult cases are lacking. We report a unique case of HPeV meningoencephalitis in an adult complicated by Refractory Status Epilepticus (RSE).